The class Diplopoda in Mongolia, with description of a new species - Mikhaljova, Elena V. (Zootaxa, 2012)
The class Diplopoda appears to be represented in Mongolia by eight species from 4 genera, 2 families (Polyzoniidae andDiplomaragnidae) and 2 orders (Polyzoniida and Chordeumatida). One species is described here as new to science: Shear-ia longa sp. nov. Genus Shearia Mikhaljova, 2000 is new to the fauna of Mongolia. All currently known Diplopoda taxa from Mongolia are keyed, including the new species. The distributions of all Mongolian diplopod species are mapped.